Project-Based Activities through Lesson Study: Improvements of Creative Thinking Performance of Pre-Service Biology Teachers in Indonesia - Nuraini, Nuraini; Asri, Indra Himayatul; Fajri, Nurul; Sarwati, Sarwati; Ariandani, Nunung (FKIP Universitas Lampung, 2022)
Implementation of Project Based Learning To Improve Creative Thinking Skills Throuh Lesson Study. Objective : This study aims to improve students' creative thinking skills by applying project-based learning through lesson study. Method: This research uses classroom action research through lesson study with three open classes with a total of 16 subjects of departement biology education, Universitas Hamzanwadi . The data were analyzed using descriptive statistics. Findings: Student activity scores during the learning process from the first, second and third open classes were 73.62%, 80.09% and 84.72% there was an average increase in activity of 5.56%. Data on students' creative thinking ability were obtained successively by 75%, 81.25% and 93.75%, there was an average increase of 9.38%. Conclusion: The application of project-based learning through lesson study can improve students' creative thinking skills. Keywords: project based learning, creative thinking, lesson study.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202206